2020
DOI: 10.3390/nu12030804
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Prediabetes in Saudi Adults: Results from an 18 Month Lifestyle Intervention

Abstract: Aim: This 18 month intervention study aims to determine the efficacy of a lifestyle modification program on prediabetes reversal among Saudi adults. Methods: An 18 month randomized, multicenter trial was conducted among Saudis with prediabetes aged 25-60 recruited from King Salman Hospital and primary care centers in Riyadh, Saudi Arabia. A total of 180 consenting individuals were randomized (1:1) to receive either intensive lifestyle intervention (ILIG) or guidance (control group, CG). ILIG was provided with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 33 publications
2
22
0
1
Order By: Relevance
“…25 Most recently, an RCT conducted in Saudi Arabia implementing an 18-months lifestyle changes intervention following the American Diabetes Association (ADA) criteria with similar age and BMI, in addition to the glucose levels 43.4±7.8, 31.3±6.4, and 6.1±0.4, respectively. 26 The study also showed similar results to Tawazon-DPP's outcomes with a significant reduction in body weight, BMI, and glucose/HbA1c. 26 However, the published study team struggled with sustaining the interest of the individuals to implement the needed lifestyle changes.…”
Section: Dovepresssupporting
confidence: 68%
See 1 more Smart Citation
“…25 Most recently, an RCT conducted in Saudi Arabia implementing an 18-months lifestyle changes intervention following the American Diabetes Association (ADA) criteria with similar age and BMI, in addition to the glucose levels 43.4±7.8, 31.3±6.4, and 6.1±0.4, respectively. 26 The study also showed similar results to Tawazon-DPP's outcomes with a significant reduction in body weight, BMI, and glucose/HbA1c. 26 However, the published study team struggled with sustaining the interest of the individuals to implement the needed lifestyle changes.…”
Section: Dovepresssupporting
confidence: 68%
“…26 The study also showed similar results to Tawazon-DPP's outcomes with a significant reduction in body weight, BMI, and glucose/HbA1c. 26 However, the published study team struggled with sustaining the interest of the individuals to implement the needed lifestyle changes. And despite this major limitation of poor compliance from the participants, the study added to the literature clinical value given the ethnic and cultural variations in response to DPPs.…”
Section: Dovepresssupporting
confidence: 68%
“…DS users make a greater effort to seek health and wellness than non-users. Our recent studies on adults reported significant positive effects on health outcomes like diabetes and metabolic syndrome in interventions that combined approaches like balanced diet and increased physical activities [32][33][34]. Such studies on children and adolescents in this region are limited.…”
Section: Discussionmentioning
confidence: 98%
“…Mathematical models predict that pre-diabetes to T2DM conversion occurs at approximately 2.5%/year, with persons of African and Asian descent being at higher risk [ 3 , 43 ]. Pre-diabetes management hinges on weight loss, and a substantial amount of work has investigated the effects of various diets [ 45 , 46 ]. In this study, participants with pre-diabetes were on average, able to surpass the recommended 5% reduction in body weight needed for T2DM risk reduction.…”
Section: Discussionmentioning
confidence: 99%